2018
DOI: 10.1002/slct.201800433
|View full text |Cite
|
Sign up to set email alerts
|

KI‐I2‐DMSO: An Improved Microwave‐Assisted Selective Oxidation of Alkenes into 1,2‐Diketones

Abstract: The microwave assisted catalytic oxidation of olefins into diketones is a remarkable effort. A new metal free, efficient catalytic system was developed for the oxidation of alkenes into α‐diketones using KI‐I2‐DMSO under microwave irradiation. With various challenging functional groups such as stilbenes, simple alkenes, alkynes, phenanthrene and 1,4‐distyrylbenzene, this environment friendly approach afforded to its corresponding products in moderate to excellent yields in 5–12 minutes under the optimized cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Our attempts to directly oxidize the double bond to the diketone were unsuccessful. 37,38 Fortunately, diol 12 was obtained by dihydroxylation of macrocyclic 4 in the presence of osmium tetroxide and NMO in 85% yield (dr = ∼4 : 1). 39 The N-methyl group was installed through a one-pot detosylation/reductive amination process 40 in readiness for the Swern oxidation 41 to deliver triketones 13 and 14 in 28% and 24% yields from two steps, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our attempts to directly oxidize the double bond to the diketone were unsuccessful. 37,38 Fortunately, diol 12 was obtained by dihydroxylation of macrocyclic 4 in the presence of osmium tetroxide and NMO in 85% yield (dr = ∼4 : 1). 39 The N-methyl group was installed through a one-pot detosylation/reductive amination process 40 in readiness for the Swern oxidation 41 to deliver triketones 13 and 14 in 28% and 24% yields from two steps, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since we have carried out many conventionally heating and microwave-assisted reactions under different environments, so the energy consumed by the reactions was calculated as we mentioned in our earlier report. [24] Herein, when the reaction reached its respective yield, we examined the energy consumptions as well as energy efficiency by the aforesaid reaction (Scheme 2). Apparently, it has been observed that for this reaction, the microwave-irradiated method is far more energy efficient and preferable than conventional heating method.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bordoloi and Tamuli described the oxidation of phenanthrene ( 23 ) via KI‐I 2 ‐DMSO‐catalyzed under microwave assistance to provide phenanthrenequinone ( 14 ) in 95 % yield in only 9 minutes (Scheme 3). [18c] Another approach to synthesizing phenanthrenequinone ( 14 ) involves the intramolecular cyclization of bisaryl derivatives bearing different substituents (Scheme 3). [19] For example, Ray and co‐worked reported the cross dehydrogenative coupling of 24 , under CuCl catalysis to achieve phenanthrenequinone ( 14 ) in 85 % yield at room temperature after 1 h of reaction [19a] .…”
Section: Synthesismentioning
confidence: 99%